IMPLEMENTASI PENDAFTARAN NIKAH SECARA ONLINE PADA MASA PANDEMI COVID-19 BERDASARKAN PERATURAN MENTERI AGAMA NOMOR 20 TAHUN 2019 TENTANG PENCATATAN PERKAWINAN - Resi Selvia; Zuraidah Azkia (Program Studi Al-Ahwal Al-Syakhshiyyah, 2021)
The occurrence of the Covid-19 virus has made people carry out all activities at home so that face-to-face-based activities are transferred online, one of which is marriage registration. The Director General of Islamic Community Guidance at the Ministry of Religion ensures that marriage registration services continue to run, marriage registration for prospective brides can be done online through the simkah.kemenag.go.id page. The formulation of the problem in this thesis (1) How is the Implementation of Online Marriage Registration During the Covid-19 Pandemic Based on the Regulation of the Minister of Religion Number 20 of 2019 concerning Marriage Registration at the Office of Religious Affairs (KUA) East Baturaja District, Ogan Komering Ulu Regency. (2) What are the Factors Affecting the Enactment of Minister of Religion Regulation Number 20 of 2019 concerning Marriage Registration at the Office of Religious Affairs (KUA) East Baturaja District, Ogan Komering Ulu Regency. This research is a field research using the type of data in this study is qualitative data, the data sources used are primary data, secondary and tertiary data, and the data obtained will be analyzed descriptively qualitatively, then will be concluded deductively. Based on the results of the study, it was found that, (1) Marriage Registration During the Covid-19 Pandemic at the Office of Religious Affairs, East Baturaja District, Ogan Komering Ulu Regency which had implemented a web-based marriage registration system through simkah.kemenag.go.id. done online. According to Circular Letter Number P-006/DJ.III/Hk.007/2020 concerning Marriage Services Towards a Covid-Safe Productive Society on the latest marriage registration through the SIMKAH program during the Covid-19 period where this online-based marriage registration system uses (e-KTP) and can be registered by themselves, but the prospective bride and groom must also come to the Office of Religious Affairs to submit the file to be checked/checked for truth which before the Covid-19 pandemic registration was still done manually. (2) The factors that influence the enactment of the Minister of Religion Regulation Number 20 of 2019 concerning Marriage Registration are the first due to the Covid-19 pandemic so that a website-based computer application with an online system is applied, namely the Marriage Management Information System (SIMKAH), which is useful for collecting data- marriage data from all Religious